Complicated pancreatic pseudocyst. Jaundice: surgical treatment - Danza, Rómulo; Danza, Franco; Fontán, Walter (Cirugía del Uruguay, 2020)
A case of an enormous pseudo-cyst of the pancreas is presented. The main symptoms were general repercussion and jaundice. The patient, during the course of its evolution, presented acute abdominal symptoms due to the rupture of the cyst in the great peritoneal cavity making it necessary to perform urgent surgery under precarious conditions. A double derivation, cysto-jejunum and cholecysto-jejunum, together with intensive medical treatment lead to the recovery of the patient.